2004
DOI: 10.1073/pnas.0400334101
|View full text |Cite
|
Sign up to set email alerts
|

Loss of chondroitin 6-O-sulfotransferase-1 function results in severe human chondrodysplasia with progressive spinal involvement

Abstract: We studied two large consanguineous families from Oman with a distinct form of spondyloepiphyseal dysplasia (SED Omani type). By using a genome-wide linkage approach, we were able to map the underlying gene to a 4.5-centimorgan interval on chromosome 10q23. We sequenced candidate genes from the region and identified a missense mutation in the chondroitin 6-O-sulfotransferase (C6ST-1) gene (CHST3) changing an arginine into a glutamine (R304Q) in the well conserved 3 -phosphoadenosine 5 -phosphosulfate binding s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
143
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 173 publications
(147 citation statements)
references
References 26 publications
2
143
0
Order By: Relevance
“…These functions are closely associated with the sulfation patterns of the CS moieties. Moreover, mutations in the genes of sulfotransferases, active sulfate synthetase or nucleotide-sugar transporters, which are indispensable for the synthesis of CS, cause chondrodysplasia in mice and humans [9][10][11][12][13][14]. These findings confirm that the sulfation of CS plays a critical role in chondrogenic differentiation.…”
Section: Introductionmentioning
confidence: 78%
“…These functions are closely associated with the sulfation patterns of the CS moieties. Moreover, mutations in the genes of sulfotransferases, active sulfate synthetase or nucleotide-sugar transporters, which are indispensable for the synthesis of CS, cause chondrodysplasia in mice and humans [9][10][11][12][13][14]. These findings confirm that the sulfation of CS plays a critical role in chondrogenic differentiation.…”
Section: Introductionmentioning
confidence: 78%
“…12 However, to the best of our knowledge, the association with neurological disorders has never been reported. The present investigation did not prove that the heterozygous ChGn-1 mutations cause neuropathy in two patients.…”
Section: Discussionmentioning
confidence: 91%
“…9 Recently, it has been reported that a broad spectrum of skeletal dysplasias result from mutations causing undersulfation of chondroitin sulfate chains in humans and in mice. [10][11][12][13][14] In contrast, no association between CSPGs and human peripheral neuropathies has been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…To date, mutations in the three CHST3 [82], CHST6 [83], and CHST14 [84] sulfotransferase genes have been recognized in cases of spondyloepiphyseal dysplasia, macular corneal dystrophy, and Ehlers-Danlos syndrome musculocontractural type 1, respectively. The CHST3 sulfotransferase catalyzes the 6-Osulfation of GalNAc in chondroitin and dermatan sulfate, whereas CHST6 catalyzes the 6-O-sulfation of GlcNAc in keratin sulfate, and CHST14 the 4-O-sulfation of GalNAc in dermatan sulfate.…”
Section: Text Box: Glycosaminoglycansmentioning
confidence: 99%